Antioxidant activities of chick embryo egg hydrolysates. Issue 1 (18th December 2013) - Sun, Hao; Ye, Ting; Wang, Yuntao; Wang, Ling; Chen, Yijie; Li, Bin
Abstract Chick embryo egg hydrolysates (CEEH) were obtained by enzymatic hydrolysis of chick embryo egg in vitro‐simulated gastrointestinal digestion. The antioxidant activities of CEEH were investigated by employing three in vitro assays, including the 2, 2′‐azinobis‐(3‐ethylbenzthiazoline‐6‐sulfonate)/1, 1‐diphenyl‐2‐picrylhydrazyl (ABTS/DPPH)/hydroxyl radical‐scavenging assays. The radical‐scavenging effect of CEEH (1.0 mg/mL) was in a dose‐dependent manner, with the highest trolox equivalent antioxidant capacity for ABTS, DPPH, and that of hydroxyl radicals found to be 569, 2097, and 259.6 μmol/L, respectively; whereas the trolox equivalent antioxidant capacity of unhatched egg for ABTS, DPPH, and that of hydroxyl radicals were found to be 199, 993, and 226.5 μmol/L, respectively. CEEH showed stronger scavenging activity than the hydrolysates of unhatched egg against free radicals such as ABTS, DPPH, and hydroxyl radicals. The antioxidant amino acid analysis indicated that the 14‐day CEEH possess more antioxidant amino acids than that of the unhatched egg. In addition, essential amino acids analysis showed that the 14‐day CEEH have the highest nutritional value. Combined with the results of the amino acid profiles, CEEH were believed to have higher nutritive value in addition to antioxidant activities than the unhatched egg.